PERAWATAN PADA MESIN EXTRUDER DENGAN MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI CV. MARSUFEB GODONG JATI - Ardhana, Ari Arya (Jurusan Teknik Mesin, Universitas Halu Oleo, 2023)
Scheduling in the production process is one factor that is quite important, scheduling can determine the time needed for the production process and predict the amount of production that will be produced by the company in a certain period. This study aims to identify and understand the maintenance process for Extruder machines using the Reliability Centered Maintenance (RCM) method. From the research results, it was found that the application of RCM focuses on the use of qualitative analysis for components that can cause failure of a system. With the highest maintenance costs found in the heating cylinder component II with 8.90%. The maintenance interval for the proposed total cost was obtained for the smallest cost found in the seal component, namely Rp. 133.43 of the actual total Rp. 138.60